Challenges and Strategies of Islamic Education Teachers in Fostering Students’ Moral Character - Nur Asiah; Muhammad Rapono (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
This study aims to analyze the challenges and strategies implemented by Islamic Religious Education teachers in fostering students’ character at SMP Al-Hidayah Medan. Using a qualitative approach with observation, interviews, and documentation techniques, it was found that PAI teachers face various internal challenges, such as declining student interest in religious subjects, limited teacher motivation and knowledge in utilizing educational technology, and a lack of variety in teaching methods. External challenges include the negative influence of social media, a global culture that promotes individualism and materialism, and minimal family support in shaping students’ character. To address these challenges, PAI teachers at SMP Al-Hidayah Medan employ active learning strategies such as discussions, case studies, and involving students in religious activities like congregational prayers and Islamic studies. Teachers also collaborate with homeroom teachers and parents to monitor students’ character development outside of school. This study emphasizes that the success of character building requires synergy between schools, families, and the community, as well as creativity and exemplary conduct from teachers to achieve optimal character education outcomes.